(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This qualitative research on postgraduate students in study groups in Colombia found that collaboration enhances training through knowledge exchange, collective construction of meanings, diversity of perspectives, and development of communication and team skills. However, obstacles such as lack of commitment, coordination problems, and imbalance in individual and group contributions can hinder this process. To improve the quality of postgraduate training, it is recommended to implement strategies that foster student commitment, effectively manage time, and balance the contributions of all group members.